Features of compiling metabolic correction programs for professional athletes and the possibility of their optimization using digital technologies - T. A. Yashin; Zh. V. Grishina; A. I. Kadykova; V. S. Feshchenko; A. V. Zholinsky; T. A. Pushkina (National Electronic Information Consortium (NEICON), 2022)
To compile a personalized program for correcting the metabolism of a professional athlete, it is necessary to take into account many factors, including age, gender, sports specialization, individual characteristics, the pathologies in the anamnesis, the stage of the athlete's training cycle, etc. When drawing up such programs for athletes of sports national teams of the Russian Federation, a scheme for assessing the characteristics of the athlete's body is used, the basis for which is information obtained during in-depth medical examinations of athletes conducted on the basis of clinics of the FMBA Russia. To improve the quality of personalized programs of metabolic correction in the future, it is possible to use professionally oriented reference intervals of laboratory blood parameters, as well as the results of genetic screening based on the strategy of complete exomic sequencing of the athlete's genome. One of the ways to increase the efficiency of metabolic correction of professional athletes is the introduction of modern information technologies and the development of a modern information system based on them. The introduction of such an information system will increase the speed of primary processing of initial information about the health status of the athlete and the peculiarities of his metabolic processes, as well as partially automate the formation of individualized recommendations regarding the diet and hydratation, and the choice of metabolic correction at various stages of the sports season.